Peningkatan Efisiensi Kompor Minyak Tanah Bersumbu Dengan Cara Meningkatkan Luas Area Api Sekunder - Sudarno, Sudarno (Jurnal Semesta Teknika, 2007)
The an perfect burning process of wick kerosene stove is one of some causes of the low efficiency of that stove. The result of temperature distribution test indicates that the temperature of secondary fire area is higher than the surrounding area. The higher temperature secondary fire area is widened by increasing the number of hole in the middle of inner muffler. Than, it is necessary to know the optimum result of increasing hole in secondary fire area toward efficiency increasing of wick kerosene stove. The test is done in the burning laboratory, machine technique Muhammadiyah University of Ponorogo by using 18 and 24 wicks kerosene stove equipped with fin reflector. The test of efficiency is done based on Profisional International Standard Testing Woodstove (VITA, 1982) nameli boilling water method. The number of passing fire holes is varied into 1 hole, 3 holes, 4 holes and 5 holes. It is found, that the widening of secondary fire area with 4 holes produces the highest efficiency in 18 and 24 wicks kerosene stove. The efficiency increasing is found as follows: 66.06 % for 1 hole, 76.06 % for 3 holes, 67.65 % for 4 holes and 66.92 % for 5 holes of 18 wick stove; and 58.41 % for 1 hole, 58.73 % for 3 holes, 60.40 % for 4 holes and 59.11 % for 5 holes ofÂ 24 wick stove.Â